Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Zoning policy performance in China: Network insights from 77 Yellow River counties in Shandong, China - Mimi Gong; Maofang Ran; Qiang Huang; Yan Cheng; Haonan Xia; Yihan Yao; Qian Wang; Wei Xiang; Meiying Jin; Zile Han; Jun Zhai; Xiaomin Li; et al. (Journal of Environmental Sciences, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Nano-architected eggshell-MoS2 reinforced MXene/CNF sandwich composite film for harsh-environment EMI shielding - Yan Zhang; Ran Wang; Ziyi Yin; Huichao Huang; Hande Wang; Houjuan Qi; Ming Wei; Dexiu Min; Xiaolin Lan; Zhanhua Huang (Chemical Engineering Journal, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Dual-motor control of a flow-induced motion energy conversion system: Device development and experimental validation - Danjie Ran; Kainan Chen; Xiang Yan; Zuhao Zhang; Wene Wang; Yuanchun Qi; Xu Yang; Zhenyu Li (Ocean Engineering, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Effects of long-term cultivation of different types of economic forests in the South China subtropics on soil bacterial communities and soil quality - Qiang Ran; Chu-Wen Qin; Guo-Hui Lu; Hui-Ping He; Qi-Lan Huang; Jia Kang; Shu Yan; Ying-Qiang Wang (Plant and Soil, 2026)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Characterization of the Trihelix Transcription Factor Family in Polygonatum kingianum and Gene Expression Pattern Analysis Under MeJA Treatment - Chun-Yu Chen; Wan-Bo Ding; Hong-Jing Zhang; Yan-Ran Qi; Wen-Xiang Wang (Plant Molecular Biology Reporter, 2025)

Self-powered broadband underwater optical communication enabled by enhanced donor-acceptor molecular junction in π-conjugated covalent organic framework - Miao Wang; Zhuang Yan; Qinbai Yun; Pei Chen; Ran Qi; Xiaotao Zhang; Kuo Yuan; Zhiyong Tang; Wenping Hu (Chemical Engineering Journal, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Effect of H2 content on the evolution process of CH4/H2 explosion pressure and flame structure - Shanshan Liu; Dongxu Huang; Yong Pan; Yingquan Qi; Lingxiu Yan; Zhenhua Wang; Xin Zhang; Ran Ye; Juncheng Jiang (Process Safety and Environmental Protection, 2025)

Potential prognostic biomarker of OSBPL10 in pan-cancer associated with immune infiltration - Jiapeng Qi; Kun Yu; Bei Liu; Yan Wang; Wei Wang; Ran An; Chaojun Wang; Na Li; Dongqian Xu; Lin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Multi-Omics Investigation of Fatty Acid Content Variations in Common Carp (Cyprinus carpio) Muscle: Integrating Genome, Transcriptome, and Lipid Profiling Data - Kaikuo Wang; Qi Wang; Yingjie Chen; Yiming Cao; Ran Zhao; Shuangting Yu; Xiaoqing Sun; Yan Zhang; Jiongtang Li (Fishes, 2025)
Fatty acids (FAs), especially the polyunsaturated fatty acids (PUFAs), play pivotal roles in growth and development. Fish possess a remarkable ability to synthesize PUFAs, rendering them a crucial and significant source of these essential FAs for human consumption. Despite extensive research on the metabolic processes of FAs, the primary processes underlying FA content variation and corresponding regulatory mechanisms remain largely unexplored. We quantified the muscular FA profiles of 304 common carp samples. High variation in muscle FA content among samples was observed, with the coefficients of variation ranging from 0.36 to 0.92. With genome-wide association studies (GWAS), we identified 1410 SNPs significantly associated with the FA content. The genetic variation at genes participating in oxidation, ubiquitination, and transcriptional factors was associated with the content of multiple FAs, while few variants were observed in the FA-synthesis genes. For the total PUFA (TPUFA) content, transcriptome analysis of groups with the highest and lowest TPUFA content identified 715 differentially expressed genes (DEGs), including genes involved in oxidation and ubiquitination. Using multiple genomic selection programs with the associated SNPs for FA content, we obtained high and positive correlations ranging from 0.65 to 0.92 between the real FA contents and estimated breeding values. These findings manifested the major-effect processes governing the differences in muscular FA content and their regulatory mechanisms. The optimal genomic selection programs provide novel and feasible perspectives to enhance FA content in common carp.

Carboniferous, not Paleoproterozoic, eclogite-facies metamorphism in the northern North China Craton as revealed by in situ garnet Lu-Hf and U-Pb geochronology - Yao-Qi Yan; Hao Wang; Jin-Hui Yang; Shi-Tou Wu; Jing Ran; Bao-Quan Zhou; Ya-Dong Wu (Earth and Planetary Science Letters, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Effects of plastic aging on biodegradation of polystyrene by Tenebrio molitor larvae: Insights into gut microbiome and bacterial metabolism - Meng-Qi Ding; Jie Ding; Shan-Shan Yang; Xin-Ran Ren; Shao-Nan Shi; Lu-Yan Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Science of The Total Environment, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Customization of indium-based MOFs for enhanced adsorptive and photocatalytic of organic pollutants: Morphology involvement on performance and mechanism - Wenliang Zhang; Yan Wang; Timing Fang; Xiao Tang; Zhezheng Ding; Yunhai Han; Ran Guo; Pengfei Qi; Xiaomin Liu (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Controls on apatite compositional variations in magmatic rocks: A case study of Mesozoic mafic–felsic intrusions from the eastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao (Journal of Asian Earth Sciences, 2024)

Recycled crustal components in the depleted mantle source: Evidence from Early Cretaceous mafic rocks in the southern margin of the North China Craton - An-Qi Wang; De-Bin Yang; Wen-Liang Xu; Hao-Tian Yang; Yi-Kang Quan; Xiang-Yu Yan; Le-Ran Hao; Feng Wang (Lithos, 2024)

Phosphorus fertiliser application mitigates the negative effects of microplastic on soil microbes and rice growth - Qi-Lu Zhuang; Hai-Yan Yuan; Jian-Qing Qi; Zhao-Ran Sun; Bao-Xian Tao; Bao-Hua Zhang (Journal of Hazardous Materials, 2024)

Exposure to fluoride exacerbates the cognitive deficit of diabetic patients living in areas with endemic fluorosis, as well as of rats with type 2 diabetes induced by streptozotocin via a mechanism that may involve excessive activation of the poly(ADP ribose) polymerase-1/P53 pathway - Jie Xiang; Xiao-Lan Qi; Kun Cao; Long-Yan Ran; Xiao-Xiao Zeng; Xiao Xiao; Wei Liao; Wen-Wen He; Wei Hong; Yan He; Zhi-Zhong Guan (Science of The Total Environment, 2024)

Insights into the long-term immobilization performances and mechanisms of CMC-Fe0/FeS with different sulfur sources for uranium under anoxic and oxic aging - Qi Fang; Yanling Tan; Ran Yan; De Zhang; Mi Li; Xiaoyan Wu; Yilong Hua; Wenjing Xue; Rongzhong Wang (Journal of Environmental Management, 2024)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

Identification of metasomatic components in lithospheric mantle under multiple tectonic regimes: Insights from Early Cretaceous mafic rocks in the northeastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Feng Wang (Lithos, 2023)

A GC/C/IRMS-based method for position-specific carbon isotopic analysis of saturated long chain fatty acids - Yu Zhao; Ran Ma; Yaoting Qi; Rong He; Zhenyu Zhu; Bo Wang; Ying Wang; Qiulin Yan; Maxime Julien; Youping Zhou (Organic Geochemistry, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

Experimental study of boiling heat transfer characteristics of metal foam porous-wall mini-channels - Guodong Xia; Yacheng Wang; Ran Li; Ziheng Yan; Qi Li (International Journal of Refrigeration, 2023)

Chloroacetonitrile exposure induces endoplasmic reticulum stress and affects spindle assembly in mouse oocytes - Feng-Xin Qiao; Ming-Xin Sun; Zhi-Ran Xu; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2023)

Efficient removal of Cr(VI) and As(V) from an aquatic system using iron oxide supported typha biochar - Yajun Cai; Zhonglyu Ran; Yan Cang; Xu Chen; Muhammad Shaaban; Qi-An Peng (Environmental Research, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Apatite geochemistry from mafic rocks in the northeastern North China Craton: New insights into petrogenesis - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Hao-Tian Yang; Feng Wang (Lithos, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Isotopic and hydrochemical analyses reveal nitrogen source variation and enhanced nitrification in a managed peri-urban watershed - Fan Yang; Jianhua Guo; Ran Qi; Changzhou Yan (Environmental Pollution, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Transcriptome sequencing and analysis for the pigmentation of scale and skin in common carp (Cyprinus carpio) - Yu-Jie Zhao; Jun Xiao; Mei-Di Huangyang; Ran Zhao; Qi Wang; Yan Zhang; Jiong-Tang Li (Molecular Biology Reports, 2021)

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Cloning and analysis of a functional promoter of fungal immunomodulatory protein from Flammulina velutipes - Wei-Ran Cong; Yan Liu; Qi-Zhang Li; Xuan-Wei Zhou (Molecular Biology Reports, 2014)

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)

Spectroscopic exploring the affinities, characteristics, and mode of binding interaction of curcumin with DNA - Xiao-Ling Li; Yan-Jun Hu; Ran Mi; Xiao-Yun Li; Pei-Qi Li; Yu Ouyang (Molecular Biology Reports, 2013)

Biophysical studies on the interactions of jatrorrhizine with bovine serum albumin by spectroscopic and molecular modeling methods - Ran Mi; Pei-Qi Li; Yan-Jun Hu; Xiao-Yang Fan; Hai-Ying Li; Xue-Cheng Yu; Yu Ouyang (Molecular Biology Reports, 2013)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Simultaneous silencing of FAD2 and FAE1 genes affects both oleic acid and erucic acid contents in Brassica napus seeds - Qi Peng; Yan Hu; Ran Wei; Yuan Zhang; Chunyun Guan; Ying Ruan; Chunlin Liu (Plant Cell Reports, 2010)